Nairobi 2012: Experience of communion and sending. Reading of the 70th Congregation of Procurators of the Society of Jesus - Álvarez de los Mozos, Francisco J. (Razón y fe, 2018)
General Congregations and their derivatives are not very frequent among Jesuits. The 70th Congregation of Procurators was held in Nairobi last July. A kind of meeting at the international level to elucidate whether a new General Congregation should be convened or not and, while they’re at it, to weigh the state of the universal Society. A new General Congregation has not been summoned, but a better and greater selection of ministries, a more active and committed apostolic creativity, have been renewed in the key of misio Dei, while it has at the same time been warned of the dangers of work overload, of activism and dispersion.